British socialism and the emotions of revolution, 1884-1926 - Carey, Michael Stephen (2018)
Spurred by recent developments in the history of emotions, this thesis looks at the place of emotion and irrationality in socialist political philosophy. I give particular attention to the shifting ways that socialists depicted the emotions of revolution. I argue that socialists had a complicated understanding of human nature, drawing on various philosophical discourses and scientific theories to grasp the ‘irrational’ and to relate it to the socialist project.